Tingkat Keterampilan Dasar Permainan Bola Voli pada Peserta Ekstrakulikuler Bola Voli - Muhamad Azis Fikri; Dayat Hidayat Dayat Hidayat; Irfan Zinat Achmad; Ruslan Abdul Gani (Peneliti.net, 2021)
This study has the objective to be achieved, which is to find out the level of Volleyball Game Basic Skills in Volleyball Extracurricular Participants in SMP Negeri 1 Tegalwaru. This research is quantitative descriptive. The method used is a survey with data collection techniques using tests and measurement of basic skills playing volleyball. The population in the study of the basic skill level of volleyball in extracurricular participants in SMP Negeri 1 Tegalwaru was volleyball extracurricular participants in SMPN 1 Tegalwaru in the 2018/2019 school year, amounting to 17 students. Subjects in this study were students who took volleyball extracurricular activities at SMPN 1 Tegalwaru as many as 17 students. Data analysis techniques using quantitative descriptive analysis as outlined in the form of percentages. Based on the results of research and discussion of the results of the basic skills test for volleyball games at SMPN 1 Tegalwaru it is known that for the category of